Adequate Compensation as a Tool for Conflict Resolution in Oil-Polluted Wetlands of Niger Delta Region of Nigeria - Oyewole Mustapha, Bello; Michael Ayodele, Olukolajo (Covenant University Journal of Politics and International Affairs, 2017)
Nigeria as a nation is battling with conflicts in virtually all geopolitical zones of the country. A major conflicting region is Niger Delta, where oil and gas resource of the nation domicile and this has become a major threat to the national development as well as the economic base of the nation. The conflict in Niger Delta has many dimensions to it and has given birth to unrepentant militant whose aim is to truncate the nation if their demands were not met. Although attempts have been made by the government at various levels as well as the multinational oil companies to address the problems emanating from the negative effect of oil and gas exploration, production and transportation in the region, the desired peace is yet to be fully realized. As part of the solution to the conflict in Niger Delta, this paper argued that adequate compensation to oil pollution victim is a right step in right direction. However, to arrive at such compensation value, there is need to review the legal framework, composition of heads of claim, as well as the procedural guide to the conduct of compensation valuation among the Nigerian Estate Surveyors and Valuers.